Clinical indications referrals – what is the risk of premalignant and malignant female genital tract disease in women referred to a dedicated nurse-led colposcopy service? A retrospective cohort study. (17th November 2022) - Barton, Florence E.; Lyon, Rachel E.; Ellis, Kay; Gillespie, Alan M.; Macdonald, Madeleine C.; Palmer, Julia E.
Abstract: Post-coital bleeding (PCB) is a poor predictive factor for cancer and should not be managed as urgent referral. Urgent referral to colposcopy is justified however, in the presence of a visible suspicion of cervical cancer. This retrospective cohort study of women attending a clinical indications referral service aims to identify the risk of pre-malignant and malignant disease in women with clinical indication referrals to colposcopy. Thirty-seven of 3521 women (1%) were diagnosed with pre-malignant cervical or endometrial disease; 14 women (0.4%) were diagnosed with cancer (11 cervix, three endometrial). To detect one cancer in women referred with an abnormal cervix, one would need to see 70 women; to detect one cancer in women referred with PCB one would need to see 790 women. Improved education in primary care and obstetrics and gynaecology training is key to improving clinical indications referral services, which is otherwise an effective and efficient service. Impact Statement: What is already known on this subject? Post-coital bleeding is a poor predictive factor for cancer and should not be considered an urgent referral. What do the results of this study add? The presence of a visible suspicion of cervical cancer however does warrant urgent referral as approximately one in 70 women will have a malignancy detected. What are the implications of these findings for clinical practice and/or further research? Improved education in primary care and obstetrics and gynaecology training is the key to improving clinical indications referral services